(untitled) (Journal of the College of Basic Education, 2026)
Wellbeing is a relatively new concept in psychology, and it has been a central focus of the field in recent decades. Psychological wellbeing leads to increased life satisfaction and indicates a difference between one’s current situation and what is perceived as an ideal standard. The emotional aspect, encompassing feelings, emotions, and sentiments, is a significant factor influencing psychological wellbeing, as it impacts an individual’s overall well-being. Life satisfaction is a crucial topic in psychology, mental health, and psychiatry. There are important indicators of an individual’s psychological well-being. The concept suggests that well-being encourages individuals to live a calm and stable life, a realistic and attainable goal. Therefore, it includes qualities such as self-acceptance, joy, and optimism. When individuals experience these qualities, they feel more well-being than ever before, especially since well-being is closely linked to life satisfaction. Based on the data, the research objectives are as follows: 1- Psychological well-being among employees. 2- The significance of differences in psychological well-being among employees according to the gender variable (male-female). 3- Employee life satisfaction. 4-Significance of differences in employee life satisfaction based on gender (male-female). 5-Correlation between psychological well-being and life satisfaction. To achieve the research objectives, the researcher developed two scales: one for psychological well-being and the other for life satisfaction. Each scale consisted of 30 items. The researcher verified the validity and reliability of both scales. The research sample consisted of 400 employees selected randomly. After processing the data using statistical methods, the following results were obtained: 1-Employees enjoy a certain level of psychological well-being. 2-There are no differences in psychological well-being based on gender among employees. 3-Employees enjoy a certain level of life satisfaction. 4-There are no differences in life satisfaction based on gender among employees. 5- There is a positive correlation between psychological well-being and life satisfaction. The results were interpreted in accordance with the adopted theories and previous studies, and in light of the results, the researcher presented a number of recommendations and suggestions.